COVID VS. NON-COVID AGE-SPECIFIC MORTALITY IN ISLAMABAD: A COMPARATIVE CROSS-SECTIONAL SURVEY - Abbasi, Fahad; Aqeel, Urooj; Aslam, Hafiz Muhammad Farhan; Umar, Maida; Gondal, Nadeem Ahmed; Zia, Muhammad Zaeem; Sikander, Siham; Hafeez, Assad (Journal of Ayub Medical College Abbottabad, 2021)
Background: COVID-19 the ongoing pandemic. Mortality due to other reasons, other than COVID-19 across age groups reduced which was anecdotally reported from Pakistan. This survey was undertaken to assess the number of deaths recorded in Islamabad from 1st March 2019 to 30th May 2019 and from 1st March 2020 to 30th May 2020 and compare the two estimates by age and gender while documenting the cause of deaths. Methods: The cross-sectional study was conducted in the Islamabad from 11th to 16th June 2020, comprising of secondary data received on age, gender, cause of death and months of death from the both, large private-public hospitals records and graveyards registers. Data was entered in both SPSS and Microsoft Excel and analysed using SPSS 22. Results: The total number of hospitals and graveyards approached in ICT were 14 and 4 respectively. The total number of deaths reported from these during March to June in 2019 and 2020 were 2,389; out of which 1,225 (51.3%) deaths were recorded in 2019 and 1,162 (48.6%) deaths in 2020. In both years, predominant variables with more mortalities were both age and gender between 61-70 years of age 511 (21.4%) 1,395 (58.4%) males respectively. Conclusion: More deaths were reported in males with old age. Cardio vascular diseases and neurological disorders were the leading causes of mortality. Not much of a larger difference in number of deaths between the both years was seen. Scarcity of data and unavailability of evidence make the anecdotal reports mere just a rumour.